Effects of community-acquired pneumonia on biventricular cardiac functions in children - Rehab Elmeazawy; Esraa Abd Al-Fattah Sorour; Al Shimaa Badreldeen (Italian Journal of Pediatrics)
Abstract Background This study aimed to evaluate the effects of community-acquired pneumonia (CAP) on cardiac function in children and compare the effectiveness of tissue Doppler imaging (TDI) and two-dimensional speckle tracking echocardiography (2D-STE) with conventional echocardiography in the early detection of biventricular cardiac dysfunction in children with CAP. Methods The study included 50 hospitalized children diagnosed with CAP and 50 matched healthy controls. All patients underwent cardiac evaluation including conventional echocardiography, TDI, and 2D-STE. Results Fifty children with CAP with a mean age of 5.02 ± 2.46 years participated in the study. Thirty-two were male (64.0%). LV systolic function (S) and RV diastolic function (E′/A′) were significantly lower in the diseased group compared to the control group (p < 0.001). The myocardial performance index (MPI) of both ventricles was significantly higher in the diseased group compared to the control group (p < 0.001). In patients with CAP, the mean value of two-dimensional longitudinal strain (2D LS) was significantly lower than that of the control group (p < 0.001). No statistically significant differences in echocardiographic parameters were observed when comparing complicated and non-complicated CAP subgroups. Conclusion TDI and 2D-STE demonstrated the ability to detect early biventricular dysfunction in pediatric patients diagnosed with CAP.